(untitled) (International Journal of Occupational Safety and Health, 2024)
Introduction: Teachers are often exposed to occupational hazards like musculoskeletal pain which may force them to early retirement from their jobs, affecting their quality of life. This study aimed to estimate the prevalence of musculoskeletal pain among government school teachers and to assess its ergonomic risk factors. Methods: A cross-sectional study was conducted among government school teachers in Kundrathur Block, Kancheepuram District, Tamil Nadu, India. The Nordic Musculoskeletal Questionnaire was used to estimate the prevalence of musculoskeletal pain. The study was conducted from June to November 2019 for 6 months. In total, 400 participants were included in the study. Descriptive statistics like frequency and percentage were used for different variables and the various risk factors as well as inferential statistics like prevalence, confidence interval, odds ratio, and chi-square test were used for finding the association between the dependent and independent variables. Results: The prevalence of musculoskeletal pain among school teachers was 69.8%. Binary logistic regression analysis showed that the factors such as sex (adjusted odds ratio [aOR] = 2.47; 95% confidence interval [CI]: 1.47-4.15) with p-value = <0.01* and number of students in each class (aOR= 1.86; 95% CI: 1.12-3.08) with p-value = <0.01* were identified to be significant risk factors associated with musculoskeletal pain. Conclusion: The prevalence of musculoskeletal pain among school teachers was found to be high. This clearly shows the significant burden of this occupational hazard on the teacher’s community, which should be addressed to focus on its prevention.